Effect of a gum‐based thickener on the safety of swallowing in patients with poststroke oropharyngeal dysphagia. Issue 11 (11th August 2019) - Bolivar‐Prados, Mireia; Rofes, Laia; Arreola, Viridiana; Guida, Sonia; Nascimento, Weslania V.; Martin, Alberto; Vilardell, Natàlia; Ortega Fernández, Omar; Ripken, Dina; Lansink, Mirian; Clavé, Pere
Abstract: Background: Increasing viscosity with thickening agents is a valid therapeutic strategy for oropharyngeal dysphagia (OD). To assess the therapeutic effect of a xanthan gum‐based thickener (Nutilis Clear ® ) at six viscosities compared with thin liquid in poststroke OD (PSOD) patients. Methods: A total of 120 patients with PSOD were studied in this controlled, multiple‐dose, fixed‐order, and single‐blind study using videofluoroscopy (VFSS). A series of boluses of 10 mL thin liquid and 2000, 1400, 800, 450, 250, and 150 mPa s viscosities were given in duplicate, interrupted in case of aspiration. We assessed the safety and efficacy of swallow and the kinematics of the swallow response. Key Results: A total of 41.2% patients had safe swallow at thin liquid which significantly increased for all viscosities from 71.9% at 150 mPa s to 95.6% at 1400 mPa s ( P < .001). PAS score (3.7 ± 2.3) at thin liquid was also reduced by increasing bolus viscosity ( P < .001). The prevalence of patients with aspiration at thin liquid was 17.5% and decreased at all viscosities ( P < .01), except at 150 mPa s. Increasing viscosity shortened time to laryngeal vestibule closure (LVC) at all viscosities ( P < .01) and reduced bolus velocity at ≥450 mPa s ( P < .05). The prevalence of patients with pharyngeal residue at each viscosity 37.7%‐44.7% was similar to that at thin liquid (41.2%). Conclusions and Inferences: The prevalence of unsafe swallow with thin liquids is very high in PSOD. Increasing shear bolus viscosity with this xanthan gum‐based thickener significantly increased the safety of swallow in patients with PSOD in a viscosity‐dependent manner without increasing the prevalence of pharyngeal residue. Abstract : This study shows a strong therapeutic effect of a gum‐based thickener on safety of swallow in post‐stroke dysphagia that depends on shear viscosity levels, and a therapeutic range of 150‐800 mPa s. Increasing viscosity shortened time to laryngeal vestibule closure at all viscosities and reduced bolus velocity at ≥450 mPa s.